2010
DOI: 10.4103/0019-5049.71046
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analgesic efficacy of buprenorphine or clonidine with bupivacaine in the caesarean section

Abstract: The need for early ambulation for caring of the neonate by mothers makes postoperative pain management after cesarean delivery unique. Favorable results have been observed with buprenorphine, clonidine and bupivacaine as epidural analgesics. This prospective, randomised triple blind control study was carried out among 112 lower segment caesarean segment (LSCS) patients, divided into three groups, to assess the analgesic efficacy and side effects of epidural analgesia, with an intermittent top up of (i) bupivac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Thus confirming the fact that a combination of an opioid and an anaesthetic augments the onset and prolongs the duration of analgesia when compared to opioid or anaesthetic alone. [1,5] Abboud et al used higher doses of buprenorphine (1 to 4 mg) alone, epidurally, found complete pain relief in 22 ± 2.4 minutes, and prolonged duration of post-operative analgesia than our combination group. [6] Studies have shown varying durations of analgesia (2.5 to 9 hours) after adminstration buprenorphine (1 to 4 mg) alone epidurally.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Thus confirming the fact that a combination of an opioid and an anaesthetic augments the onset and prolongs the duration of analgesia when compared to opioid or anaesthetic alone. [1,5] Abboud et al used higher doses of buprenorphine (1 to 4 mg) alone, epidurally, found complete pain relief in 22 ± 2.4 minutes, and prolonged duration of post-operative analgesia than our combination group. [6] Studies have shown varying durations of analgesia (2.5 to 9 hours) after adminstration buprenorphine (1 to 4 mg) alone epidurally.…”
Section: Discussionmentioning
confidence: 51%
“…This is in accordance with that of Agarwal et al (170 minutes). [1,7] We found that buprenorphine showed a improved quality of analgesia regarding VAS scale. This is in accordance with that of Agarwal et al Abboud et al also found a significantly improved quality of analgesia in patients who recieved epidural bupivacaine with buprenorphine than with bupivacaine alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrathecal buprenorphine in doses of 75 µg induces rapid onset of analgesia and lacks the side effects that can be attributed to higher doses. 10 Dixit et al stated that 60 µg buprenorphine given intrathecally to pregnant patients prolonged the duration of analgesia with negligible sideeffects. 11 Clonidine prolongs the duration of intrathecally administered local anesthetics and has potent antinociceptive properties.…”
Section: Discussionmentioning
confidence: 99%